Design and testing of a prototype foot orthosis that uses the principle of granular jamming. Issue 3 (13th June 2021) - Simonds, Emily; Colton, Jonathan; Kogler, Geza; Chang, Young-Hui
Abstract : Study Design: A mechanical testing protocol was used to compare the material properties of commercially available foams with that of a newly designed granular jamming orthosis prototypes. Background: Foot orthoses have an inherent limitation of predetermined mechanical material properties coupled with a fixed orthotic interface shape that cannot be readily changed. Objectives: To develop and test a novel orthotic insole design concept that incorporates principles of granular jamming. Methods: Granular media were used in combination with vacuum pressure to create a variable stiffness granular foot orthosis. Four types of granular media (rice, poppy seeds, micropolystyrene, and polystyrene beads) were tested in different prototype configurations varying in volume fill and particulate size. Stress–strain curves were obtained from uniaxial compression tests to characterize granular foot orthosis prototypes in comparison with commercial orthotic foams. Results: Increasing vacuum pressure increased prototype stiffness for most configurations. A single granular jamming orthosis could exhibit energy absorption values that spanned the entire commercial foam performance range, and in some cases extended far beyond the upper values of the tested foams. Conclusion: The results suggest that granular jamming principles can provide clinicians the capability for rapid selection of mechanical properties over a wide range of orthosis stiffnesses. Importantly, patients could don the orthosis because the clinician makes real-time assessments and adjustments in the clinic.